PERANAN KEPALA SUKU MONI DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN DI DISTRIK WANDAI KABUPATEN INTAN JAYA PROVINSI PAPUA). - BAGAU, JELIDA; Rompas, Wilson; Plangiten, Novva (Sam Ratulangi University, 2016)
ABSTRACT: As it is known that the Organization of Indigenous Peoples is one container to collectand bamboozle indigenous peoples so that the role of traditional leaders more directly in supportingthe wheels of government in the implementation of development and provide guidance to the publicas mandated. In Law No. 21 of 2001 on Special Autonomy for Papua Province. Containing organizeand manage their own household / own government. Chieftain, is not set in legislation, but in the Act.No. 21, 2001, Article 1 Paragraph 13 of the